2013
DOI: 10.2322/tastj.11.99
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Three-Dimensional Flexible Parachute System under Supersonic Conditions

Abstract: In the present study, the supersonic flow over a three-dimensional flexible parachute system is numerically simulated using a simple "immersed boundary method" together with the weak fluid-structure coupling scheme. The parachute system employed here consists of a capsule and a canopy. The mass-spring-damper model is applied to solve the structural dynamics of the flexible parachute system. The objective of this study is to analyze the effects of aerodynamic interaction such as wake/shock interaction on the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It was also found that the sting between the canopy and capsule has a rather small effect on the flow field and pressure distribution on the body surfaces, and the pulsation mechanism for the case without a sting is identical to that for the case with a sting. Xue et al [8] conducted the simulations of three-dimensional (3-D) flexible supersonic parachute system and found that there are two key factors for the dynamics of the parachute system: the unsteady change in canopy shape and the aerodynamic interference between the capsule wake and the canopy shock. Xue et al [9] performed the simulations of supersonic parachute system with canopy shrouds, and shock waves are generated upon the canopy shrouds, which exacerbate the flow field instability.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the sting between the canopy and capsule has a rather small effect on the flow field and pressure distribution on the body surfaces, and the pulsation mechanism for the case without a sting is identical to that for the case with a sting. Xue et al [8] conducted the simulations of three-dimensional (3-D) flexible supersonic parachute system and found that there are two key factors for the dynamics of the parachute system: the unsteady change in canopy shape and the aerodynamic interference between the capsule wake and the canopy shock. Xue et al [9] performed the simulations of supersonic parachute system with canopy shrouds, and shock waves are generated upon the canopy shrouds, which exacerbate the flow field instability.…”
Section: Introductionmentioning
confidence: 99%
“…However, their conditions were limited to very low speed (0.6-1.2 m∕s). Xue and Nakamura [9] and Xue et al [10,11] conducted a series of studies on supersonic parachutes. In Refs.…”
mentioning
confidence: 99%
“…The effect of separation distance was surveyed in Ref. [9] for a flexible canopy. All these findings were of great importance, but they assumed laminar flows throughout their papers.…”
mentioning
confidence: 99%